Implementation of a Contextual Approach in Islamic Religious Education Learning to Form the Character and Islamic Life Ethos of Khairunnas Middle School Students in Tuban - Muhammad Khusain Muslimin; Irfan Gutawa (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to examine the implementation of the contextual teaching approach in Islamic Religious Education (PAI) at SMP Khairunnas Tuban, as well as to identify the supporting factors, obstacles, and its impact on shaping students’ Islamic character and work ethics. This approach is considered essential because it connects the instructional material with students’ real-life experiences, enabling the learning process to become more relevant and meaningful. The study employs a qualitative research method with a descriptive design. Data were collected through in-depth interviews, classroom observations, and documentation review. The research subjects consisted of Islamic Religious Education teachers and eighth-grade students. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. This study provides a comprehensive illustration regarding the effectiveness of contextual teaching in fostering Islamic character among students. The findings show that the contextual approach has been implemented well, although it is not yet consistent and lacks variety in instructional methods. This approach has succeeded in improving students’ understanding of Islamic values and encouraging the application of Islamic work ethics in daily life. Supporting factors include the religious school environment and the teacher’s competence, while the obstacles arise from limited variation in teaching methods, time constraints, and insufficient contextual learning media. The study recommends the development of more creative teaching strategies and the use of more contextual media, as well as expanding the research scope to various Islamic schools to obtain more comprehensive and sustainable results.